2005
DOI: 10.1017/s0021932005007182
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Malaria and Mosquito Avoidance in Relation to Household Risk Factors in a Kenyan Coastal City

Abstract: SummaryA geographically stratified cross-sectional survey was conducted in 2002 to investigate householdlevel factors associated with use of mosquito control measures and self-reported malaria in Malindi, Kenya. A total of 629 households were surveyed. Logistic regressions were used to analyse the data. Half of all households (51%) reported all occupants using an insecticide-treated bed net and at least one additional mosquito control measure such as insecticides or removal of standing water. Fortynine per cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
3
13
2
Order By: Relevance
“…Other studies have shown that use of malaria prevention measures has been directly related with higher educational level. 31 However, this finding is not compatible with the result of other similar studies. 20,29 The variation observed may be explained by the differences in methodological approach among studies and socioeconomic variation of study participants.…”
Section: Discussioncontrasting
confidence: 85%
“…Other studies have shown that use of malaria prevention measures has been directly related with higher educational level. 31 However, this finding is not compatible with the result of other similar studies. 20,29 The variation observed may be explained by the differences in methodological approach among studies and socioeconomic variation of study participants.…”
Section: Discussioncontrasting
confidence: 85%
“…Other studies have shown that use of malaria prevention measures has been consistently related to higher maternal education (e.g. Keating et al 2005; Noor et al 2006), yet we saw no notable associations between use of preventive measures, including bednets, and malaria risk except for a modest decreased risk among those using mosquito coils. In our study, as in that by Brooker et al (2004), practice of preventive measures was quite low.…”
Section: Discussioncontrasting
confidence: 72%
“…Initially studies focused on malaria transmission dynamics and high incidence of severe malaria [14-17], but surprisingly found lower transmission than in western Kenya – providing evidence that high incidence of severe malaria can occur even at relatively low intensities of transmission [16,17]. These studies were proceeded by investigations of mosquito blood-feeding behaviour [15,18], vector distribution patterns [19,20], spatial-temporal variations in malaria prevalence and intensity of transmission [20], vector population genetics [21], community-based vector control [22,23], malaria vector control [24-26] and larval ecology of malaria vectors [27-29]. …”
Section: Introductionmentioning
confidence: 99%